The Reinsurer’s Subrogation in Colombia - Coronado Sabogal, Diego Alejandro (Revista Ibero-Latinoamericana de seguros, 2024)
Taking into account the legal and reinsurance business evolution, the judicial challenges that the reinsurance industry in Colombia has recently faced and the growing placement of insurance programs through the fronting scheme, it is pertinent and adequate to examine the reinsurer’s possibility to take over the position of the insurance company (cedant), to exercise its rights against the responsible for the loss suffered by the insured, once the original insured has been previously and effectively compensated. This document seeks to examine and clarify the possible paths to exercise the reinsurer’s subrogation under the Colombian legislation, being an issue that has not been fully explored by the national doctrine and that aims to represent an essential tool for the reinsurer in the post-claims stage, more precisely, once the compensation derived from the reinsurance contract has been recognized to the cedent (insurance company) or directly to the original insured.